PENGARUH KEKERASAN ORANG TUA TERHADAP KEPERCAYAAN DIRI ANAK DI DESA BATEH TANGAH NAGARI AMPEK KOTO PALEMBAYAN KEC. PALEMBYAN - Zulna Jaziila; Fadhilla Yusri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This research is motivated by the existence of problems related to parental violence which causes children's self-confidence to be disturbed. The aim of this research is to determine the influence of parental violence on children's self-confidence in Bateh Tangah Nagari Village Ampek Koto Palembayan District. Palembayan. The type of research carried out is quantitative correlational research, namely to see the influence of something, see whether there is an influence of X on Y, where the results of this research are in the form of numbers. The population in this study was 80 people consisting of 45 women and 35 men. Meanwhile, the sample in this study consisted of 20 children aged 7-12 years using purposive sampling techniques. Data were collected using a questionnaire instrument, which had been validated first and then processed using a simple non-parametric linear regression test using SPSS version 22. The constant number of Unstandardized Coefficients in this study was 90,080. This means that if there is no parental violence (X), the consistent value of self-confidence (Y) is 90,080. The regression coefficient value is 7330. This figure means that for every 1% increase in the level of parental violence (X), self-confidence (Y) will decrease by 7330, so the regression equation is Y`=90.08 -7330 X.